2006
DOI: 10.1182/blood-2005-11-026963
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the essential nutrient isoleucine in human erythrocytes infected with the malaria parasite Plasmodium falciparum

Abstract: The intraerythrocytic malaria parasite derives much of its requirement for amino acids from the digestion of the hemoglobin of its host cell. However, one amino acid, isoleucine, is absent from adult human hemoglobin and must therefore be obtained from the extracellular medium. In this study we have characterized the mechanisms involved in the uptake of isoleucine by the intraerythrocytic parasite. Under physiologic conditions the rate of transport of isoleucine into human erythrocytes infected with mature tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 37 publications
4
117
1
Order By: Relevance
“…Additionally, homologs of the prokaryotic transcription effector RelA, which regulates the amino acid starvation response in bacteria (35), could not be identified in the parasite. Although infected RBCs reportedly take up amino acids, including isoleucine, an order of magnitude more efficiently than uninfected RBCs (36), expression of putative amino acid transporters (e.g., PFL1515c, PF11_0334, and PFL0420w) was not up-regulated during starvation (Dataset S3). Field isolates of P. falciparum exhibit differential expression profiles, including one described as having starvation-response characteristics (37).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, homologs of the prokaryotic transcription effector RelA, which regulates the amino acid starvation response in bacteria (35), could not be identified in the parasite. Although infected RBCs reportedly take up amino acids, including isoleucine, an order of magnitude more efficiently than uninfected RBCs (36), expression of putative amino acid transporters (e.g., PFL1515c, PF11_0334, and PFL0420w) was not up-regulated during starvation (Dataset S3). Field isolates of P. falciparum exhibit differential expression profiles, including one described as having starvation-response characteristics (37).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Ile is one of the most abundant amino acids in malaria proteins it is nevertheless absent from host haemoglobin and therefore the parasite must source this amino acid from the extracellular milieu (24). The parasite achieves this by exchanging intracellular leucine by a two-step process that involves an ATPindependent transporter capable of exchanging intracellular leucine for isoleucine, followed by the ATP-dependent storage or accumulation of isoleucine within the parasite (25). These data lead us to speculate that the essential nature of the Leu-specific Pf A-M17 may relate to the requirement for an ample supply of free leucine within the malaria cytosol to exchange for isoleucine.…”
Section: Discussionmentioning
confidence: 99%
“…Within the parasite cytosol, PfM17LAP may be important in the terminal stages of protein/peptide turnover. 30,31,41,45 The almost exclusive specificity of PfM17LAP for leucine suggests that this enzyme may be essential for the generation of free leucine that can be exchanged for extracellular isoleucine 12,31 , an aminoacid that cannot be synthesized by the parasite and is the only aminoacid not found in human haemoglobin. Naughton et al 8 reported that bestatin, at 5-and 25-fold its IC 50 , reduced the up-take of isoleucine into P. falciparum cells in vitro by 20-25 and 50%, respectively, which may support this idea.…”
Section: Do Pfm1aap and Pfm17lap Function In The Same Or Different Cementioning
confidence: 99%
“…Malaria parasites also have the ability to synthesize several aminoacids de novo (including asparagine, glutamine, glycine, proline, aspartate and glutamate) and can acquire additional aminoacids from exogenous sources such as host plasma. 10,11 Isoleucine, which is the only aminoacid absent from human haemoglobin, is obtained from outside of the red blood cell by exchanging it with leucine, an abundant aminoacid in haemoglobin 12 . Malaria parasites have been shown to grow in culture medium lacking all aminoacids except isoleucine.…”
Section: Introductionmentioning
confidence: 99%